Рассказы из русской истории - Алексеев Сергей Петрович (Библиотека "Дружбы народов", 1991)
Экземпляры: ф.7 (1991) / Инвентарный номер: 33766 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 47 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6-44